Analisis Kepuasan Pengguna Aplikasi ChatGPT Menggunakan Metode E-Serqual (Studi Kasus : Mahasiswa/I Universitas Dinamika Bangsa) - Mulyanto, Ade; Istoningtyas, Marrylinteri (LPPM STIKOM Dinamika Bangsa, 2024)
The ChatGPT application provides natural language processing (NLP) technology capable of responding to human questions in the form of text (referred to as Prompts) typed into the application. The author conducted this research to determine the extent of the impact of user satisfaction on the ChatGPT application. The method used is the E-SERVQUAL method, with a sample of 360 respondents and data analysis performed using SPSS software. The results of the validity and reliability tests indicated that all data in this study were valid and reliable. The research findings show that out of the seven E-SERVQUAL variables, only five—Fulfillment, System Availability, Responsiveness, Compensation, and Contact—significantly affect user satisfaction with the ChatGPT application.